The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/aphw.12070
|View full text |Cite
|
Sign up to set email alerts
|

Food for Thought: A Randomised Controlled Trial of Emotional Freedom Techniques and Cognitive Behavioural Therapy in the Treatment of Food Cravings

Abstract: Addressing the internal determinants of dysfunctional eating behaviours (e.g. food cravings) in the prevention and treatment of obesity has been increasingly recognised. This study compared Emotional Freedom Techniques (EFT) to Cognitive Behavioural Therapy (CBT) for food cravings in adults who were overweight or obese (N = 83) in an 8-week intervention. Outcome data were collected at baseline, post-intervention, and at 6- and 12-months follow-up. Overall, EFT and CBT demonstrated comparable efficacy in reduci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 65 publications
4
35
2
3
Order By: Relevance
“…This again illustrates that focusing on emotion regulation skills in a standardized behavioural weight loss intervention may help in weight reduction in obese individuals and that adding emotional-eating specific strategies may not provide additional benefits in the short term. Similar findings were found by Stapleton et al (2016) [37] comparing an intervention in emotional freedom technique (EFT) with cognitive behavioral therapy. Also in this randomized controlled trial, both intervention groups had similar treatment effects regarding weight as well as psychological outcomes within a 12 months follow up.…”
Section: Discussionsupporting
confidence: 86%
“…This again illustrates that focusing on emotion regulation skills in a standardized behavioural weight loss intervention may help in weight reduction in obese individuals and that adding emotional-eating specific strategies may not provide additional benefits in the short term. Similar findings were found by Stapleton et al (2016) [37] comparing an intervention in emotional freedom technique (EFT) with cognitive behavioral therapy. Also in this randomized controlled trial, both intervention groups had similar treatment effects regarding weight as well as psychological outcomes within a 12 months follow up.…”
Section: Discussionsupporting
confidence: 86%
“…While speculatively, the neural changes indicated in this pilot study appear to compare to the self-reported food craving decreases in the current trial as well as previous EFT and food craving trials [19][20][21][22]. The lack of engagement in homework activities reported by participants (addressed next) and the relative deactivation of the brain activity during the post scans while viewing high caloric food images, suggests a correlation worth examining in larger future trials.…”
Section: Discussionmentioning
confidence: 48%
“…Finally and worthy of note is that while the EFT participants were encouraged to engage in the technique outside sessions, and reminder messages were sent by the lead therapist between sessions every week. However, they typically did not do so via self-report and this was also indicated in previous trials [19][20][21][22]. A recent two year follow-up of an 8-week online intervention program for overweight or obese adults found participants' food craving, perceived power of food, dietary restraint capabilities and all psychological distress symptoms (i.e.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations